I saw the following differential equation/solution in a paper and it is puzzling me. Any help with regards to the nature of this differential equation (with partial sum as coefficient?) or the specifics of the derivation are highly appreciated!

.... Y(t) must satisfy the differential equation

-$\frac{d}{dt} Y(t) = a^{-1}\left[1+\sum_{i=1}^{N}b_i\right]Y(t)$

with the initial condition Y(0)=1. Integration yields

$Y(t)=e^{-t/a} \Pi_{i=1}^N e^{-(t/a)b_i}$


closed as unclear what you're asking by zhoraster, user91500, TastyRomeo, Namaste, Daniel W. Farlow Feb 2 '17 at 13:25

Please clarify your specific problem or add additional details to highlight exactly what you need. As it's currently written, it’s hard to tell exactly what you're asking. See the How to Ask page for help clarifying this question. If this question can be reworded to fit the rules in the help center, please edit the question.


The equation is just $$Y't()=A Y(t)$$ which gives $$Y(t)=C e^{At}$$ and the condition gives $C=1$. So $$Y(t)=\exp\left(-\frac{1+\sum_{i=1}^n b_i} a t\right)$$ which write $$\log(Y(t))=-\frac t a-\frac{\sum_{i=1}^n b_i} a t=-\frac t a-\frac{b_1} a t-\frac{b_2} a t-\frac{b_3} a t+\cdots$$ $$Y(t)=\exp(-\frac t a)\exp(-\frac{b_1} a t)\exp(-\frac{b_2} a t)\exp(-\frac{b_3} a t)\cdots\exp(-\frac{b_n} a t)$$ whic is your formula.


Not the answer you're looking for? Browse other questions tagged or ask your own question.